Investigating factor interactions in formalising the process of developing new products - Stoycheva, Bozhana Yavorova; Antonova, Diana Antonova (Serbian Journal of Management, 2018)
The creation of new product development programmes in industrial organisations, as a process involves a system of activities for defining, planning and implementing projects, with a view to successful market realisation. The success of a programme and its associated projects is not unambiguous (depends to some extent on the participants' point of view) and can be related to the achievement of predetermined goals and constraints, customer satisfaction, organisational knowledge, etc. For the respective industrial company, the planning process is more important than the plan itself, because hypotheses are checked; comparable alternatives are analysed; the future consequences of one or another of today's decisions are investigated; the necessary changes to the prerequisites are made.The survey was conducted in 560 medium and large enterprises operating in the manufacturing industry of Bulgaria. The aim is to establish independent factor variables and their value impacts on the effective management of the process of developing new products related to the dependent variable "formalisation or use of officially documented procedures describing the new product development (NPD) process".In order to meet the target, a quantitative study was carried out by applying a correlation and regression analysis to search for relationships and dependences between the variables examined. A regression model is presented for the dependent variable studied. The results and recommendations obtained can be used to improve the management of the product innovation process.
Keywords: factor analysis; formalisation of NPD; new products development (NPD); innovation process